Redirected Zn Electrodeposition by an Anti‐Corrosion Elastic Constraint for Highly Reversible Zn Anodes. (13th May 2020) - Zhao, Ruirui; Yang, Ying; Liu, Ganxiong; Zhu, Renjie; Huang, Jingbo; Chen, Zhiyuan; Gao, Zhonghui; Chen, Xiao; Qie, Long
Abstract: With advantages such as high theoretical capacity, low cost, and nontoxicity, Zn metal has been widely investigated as an anode for aqueous batteries. However, the problems of dendrite formation and sustained corrosion originating from severe interfacial side reactions and uncontrolled Zn electrodeposition in aqueous electrolytes significantly slows down the practical application of Zn metal anodes. To address these issues, herein, an anti‐corrosion elastic constraint (AEC) is introduced that is built with nanosized TiO2 and polyvinylidene fluoride (PVDF) matrix to Zn anode, where the PVDF layer serves as an elastic H2 O/O2 ‐blocking layer and the decorated TiO2 nanoparticles assist uniform Zn electrodeposition. With this corrosion‐inhibition and electrodeposition‐redirection coating, the electrodeposition consistency and thermodynamic stability of the Zn anode are significantly improved, enabling a long‐term stable plating/stripping performance for 2000 h with an ultralow overpotential (<50 mV) and a high average Coulombic efficiency (>99.4%) for 1000 cycles without obvious dendrite formation. Even at a high current density of 8.85 mA cm −2 with limited Zn supply (DODZn = 60%), stable Zn deposition is achieved over 250 h. When coupled with a MnO2 cathode, the AEC‐Zn anode shows a remarkably enhanced full‐cell cycling stability, indicative of high reliability of aqueous Zn batteries for practical application. Abstract : An anti‐corrosion elastic constraint is developed to redirect the Zn electrodeposition for aqueous zinc‐ion batteries. With this corrosion‐inhibition and electrodeposition‐redirection coating, the electrodeposition consistency and thermodynamic stability of Zn anodes are significantly improved, enabling a long‐term stable plating/stripping performance for 2000 h with an ultralow overpotential (<50 mV) and a high Coulombic efficiency (>99.4%) for 1000 cycles.